Stress, Professional Lifestyle, and Telomere Biology in Elite Athletes: A Growing Trend in Psychophysiology of Sport - Mehrsafar, Amir Hossien; Serrano Rosa, Miguel Angel; Moghadam Zadeh, Ali; Gazerani, Parisa (Frontiers in Psychology, 2020)
Professional lifestyle and championship period often put a great deal of pressure on athletes, who usually experience highly stressful periods during training for competitions. Recently, biomarkers of cellular aging, telomere length (TL) and telomerase activity (TA), have been considered to investigate the effects of stress and lifestyle factors. Studies in non-athletic populations have shown that stress and poor lifestyle decrease TL and TA. On the other hand, it has been shown that in general, exercise increases TL and its activity, although the underlying mechanisms remained largely unexplored. TL and TA outcomes in elite athletes remains inconclusive and mainly affected by confounding factors, such as age. Elite athletes, therefore, might offer a unique target group for studying exercise-telomere hypothesis for further investigation of the roles of stressors on telomere-related biomarkers. In this perspective, we highlight the potentials for studying these psychophysiological markers in elite athletes in order to understand stress-aging relationship and potential underlying mechanisms. Moreover, we present important methodological aspects that could help in the development of future experimental designs.